The impact of student academic achievement on graduate salaries: the case of a leading Russian university. Issue 2 (17th February 2019) - Rudakov, Victor; Roshchin, Sergey
ABSTRACT: This paper analyses the impact of academic achievement on future salaries by looking into the grade point average (GPA)-earnings relationship for graduates of a leading Russian university. The study is based on pooled cross-sectional graduate survey data for 2014–2015. The issue of how student academic achievement impacts future labour market rewards is analysed through academic, demographic and labour market factors. We found that there is a significant positive impact of GPA on salaries of BA graduates (9–12% wage premium for an additional GPA point) and an insignificant or negative impact for MA programmes graduates. The study depicts that this negative effect can be partially explained by employment sector-specific variables. Among the main factors which positively affect earnings of graduates is work experience. Graduates who combined study and work achieve a 30% wage premium. However, there is no evidence that combining study and work affects student academic achievement, even for those who combined studies with full-time job. Despite the higher GPA of female students, male graduates' earnings are 18% higher. Gender wage differences can be explained by gender distribution by the sector of employment: the over-representation of women in the low-paid education and science sectors and their under-representation in entrepreneurship and corporate sector.